Increasing the Competitiveness of MSME Products through Obtaining Basic Licensing to Support the Availability of Clean and Halal Standard Products - Roanisca, Occa (Fakultas Teknik, Universitas Bangka Belitung, 2023)
The Indonesian government has always paid considerable attention to the existence and development of Micro, Small and Medium Enterprises (MSMEs). This is because the number of MSMEs in Indonesia is very large, and MSMEs are able to absorb a high enough workforce with small business capital that easily adapts to market needs. The current era of digitalization requires MSME players to maximize promotional and marketing activities online. Besides that, MSMEs must obtain basic permits such as IUMK, HS and PIRT permits. Sinar Jaya Jelutung Village is located in Bangka Regency, has 98 MSME units. MSMEs that have pocketed new permits are 34%. The type of MSME cultivated by the community in the Sinar Jaya Jelutung Village is processed food. MSMEs do not yet have an online market place to sell MSME products online. Therefore, there is a need for assistance for MSMEs in the Sinar Jaya Jelutung Village to create technology-based and competitive businesses. To realize this there are several problems that partners (MSMEs) have, namely: lack of knowledge regarding clean standard production processes, and procedures for registration to obtain IUMK, HS and PIRT permits. Another problem that partners have is limited knowledge in using technology for promotion and marketing, so they have not reached a wider market share. Solutions that can be offered are to help partners by increasing knowledge about production processes with clean standards by conducting direct coaching to partners, facilitating the registration of IUMK permits, Certificates of Eligible Hygene Sanitation and PIRT. In order to reach a wider market share and to have strong coordination among MSME players, training was conducted on registration and design of packaging stickers for the promotion and marketing of all MSME products in the Sinar Jaya Jelutung Village. Community service activities with targeted partners for MSME actors in the Sinar Jaya Jelutung Sub-District are running smoothly and well, so they can achieve the set targets. This community service activity is in the form of outreach and direct assistance to target partners. The knowledge and awareness of MSME actors has increased regarding the submission of product legality, at the end of the activity all MSME actors already have NIB and PIRT certificates. Awareness of having attractive and informative packaging stickers is increasing, MSME players have received packaging stickers to support product promotion.